Needlescopic surgery for broad ligament hernia: A case report. Issue 1 (14th February 2019) - Koizumi, Noriaki; Ariyoshi, Yosuke; Fujiki, Hiroshi; Sakakura, Chouhei
Abstract : Broad ligament hernia is a rare type of internal hernia. We herein report a case of broad ligament hernia successfully treated by needlescopic surgery. A 41‐year‐old woman was referred to our hospital with a complaint of nausea and vomiting. Abdominal contrast‐enhanced computed tomography showed diffuse dilatation of the small bowel accompanied by a caliber change at the right side of the uterus. She was thus diagnosed with small bowel obstruction due to incarceration through right broad ligament hernia. After bowel decompression, she underwent elective needlescopic surgery using 2‐ and 3‐mm instruments. The defect in the right broad ligament was closed with sutures, and she was discharged 2 days after surgery. In the treatment of broad ligament hernia without bowel ischemia, neither an abdominal incision nor any energy devices are required. In this respect, needlescopic surgery seems to be a promising approach among minimally invasive surgeries.